GEOTECHNICAL INVESTIGATION FOR EVALUATING COAL MINING DESIGN OF PIT A AT KUTAI KERTANEGARA, EAST KALIMANTAN - Agus Nugroho (Indonesian Mining Journal, 2014)
Due to the occurrence of slope failure at Pit A, on both side-wall and low-wall geotechnical study had been con- ducted to evaluate the slope stability whether the mining can be continued through the end of mine life or not. Slope stability modeling using Limit Equilibrium method shows that coal mining is feasible to reach the depth of ± 50m as stated in a previous plan. The previous design for sidewall has the overall slope of 400. This is not a stable condition with Safety Factor (SF) =1.050. As a result, evaluation of slope design must be conducted. The simulation shows that the slope must be changed to 300 in terms of reaching stable condition with SF=1.539. Previous design of the low wall that has the overall slope of 300 is stable with the SF=1.359 however, as the area is near settlements and Mahakam River, the pit slope must be reduced to 250 with SF=1,523. Slope stabil- ity simulation at the high-wall shows that the previous design with the overall slope 450 is stable for SF=2.418. It is not necessary to change previous design. However, to guaranty safety condition along mining area, it is recommended to make safety-berm to prevent the rocks enter the area.